The Effects of Broken Home Families on Grade VI Elementary School Students' Moral and Psychic Development - Eliyil Akbar; Irfan Tamwif (Ananda: Jurnal Pendidikan Anak dan Remaja, 2025)
This study was motivated by empirical findings of teachers at SDN 1 Sribitan, which indicated that students from broken homes often cause disturbances in the classroom during the learning process. This behavior is thought to be a form of seeking attention from the surrounding environment. Based on this phenomenon, the researcher was interested in conducting a case study to examine more deeply the impact of broken home family conditions on the moral and psychological development of elementary school students. This study used a qualitative approach with a case study method. Participants were selected purposively based on family background and prominent behavior at school so that two students from grade VI, namely A.C.P. and P.D.A., were selected from five students with similar backgrounds. The results of the study showed that broken home families have a significant influence on children's moral and psychological development. This impact is reflected in the behavior of participants, which is characterized by difficulty apologizing when making mistakes, often causing noise in class, and disobedience to school rules. This study emphasizes the importance of special attention and handling of students with an incomplete family background in order to support their character development and psychological well-being.